THE IMPORTANCE OF HEART RATE MONITORING IN SPORTS MEDICINE (SCIENCE TIME JOURNAL, 2026)
Heart rate monitoring is an important component of modern sports medicine and plays a significant role in evaluating athlete health, physical fitness, and athletic performance. This article examines the importance of heart rate monitoring in sports medicine through an analysis of recent scientific literature. Particular attention is given to the role of heart rate assessment in regulating training intensity, monitoring cardiovascular function, preventing overtraining syndrome, and supporting rehabilitation programs. The study also discusses the application of modern wearable technologies for continuous heart rate monitoring during training and competition. The reviewed literature indicates that regular heart rate assessment provides valuable information regarding physiological adaptation,recovery status, and exercise tolerance. Furthermore, heart rate monitoring contributes to the early detection of potential cardiovascular abnormalities and helps optimize individualized training programs. The findings confirm that heart rate monitoring is a reliable, non-invasive, and effective tool for improving athlete safety, enhancing performance, and supporting evidence-based sports medicine practice.